(untitled) (Research Nepal Journal of Development Studies, 2019)
Religion is an opium of the society as Karl Marx claims but the ultimate stage of human development is scientific communism which is approximately equal to Buddha’s meaning of Sangha. To analyze the final stage of human development by Marxian philosophy and Shakyamuni Buddha’s philosophy on the concept of Sangha, the study is being conducted. Methodologically, the study has analyzed the meaning of Sangha of Buddha and different stages of human development of Marxist’s communism from relevant literatures. Ultimately there is not any significant value of personal property in both ideologies.